PERAN PENDIDIKAN JASMANI DALAM MENINGKATKAN LITERASI FISIK ANAK SEKOLAH DASAR - Kusuma, David Anggar (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
Physical education as a forum for education carried out through physical activities has an important role in improving children's physical literacy. Various strategies need to be carried out by physical education teachers in order to make it happen. Physical literacy which contains knowledge and understanding, physical competence, motivation, and self-confidence is a concept that is very important for students to understand and have, so schools design student-oriented programs to be implemented by physical education teachers and other teachers. The implementation of a program implemented by teachers certainly needs to get help, support, and cooperation from parents of students and all school stakeholders. The purpose of this research is to find out what the role of physical education is in improving children's physical literacy. The method used in carrying out this research is literature review, where this research is carried out by conducting a study of the results of previous studies based on theories that can be accounted for to produce new and more up-to-date theories. The results of the interpretation of cause and effect of 8 articles that are relevant to the research keywords, namely children, physical literacy, and physical education, can be concluded that physical education has a very important role in improving children's physical literacy, namely by using fun games and professional development of teachers can increase children's physical literacy which has an impact on increasing physical activity and an active and healthy living culture throughout life.